Drinking Patterns and Behavioral Consequences: A Cross-Sectional Study Among Romanian University Students - Adriana Nasui Bogdana; Popa Monica; Alina Popescu Codruta (Sciendo, 2016)
Alcohol/binge drinking among university students has become a major public health problem. Many of young students will be exposed to substantial changes in living arrangements, socialization groups and social activities during the transitional period.